Bibliometric Analysis of E-Government and Trust: A Lesson for Indonesia - Abdul Halil Hi Ibrahim; Tawakkal Baharuddin; Marno Wance (Jurnal Borneo Administrator, 2023)
The development of digitalisation has spectacularly affected global society, including Indonesia. Many governments are aware of the opportunities and benefits of this development, so they carry out digital transformation and adaptation through e-government systems. However, public trust emerges as one of the determining factors in assessing the success of implementing e-government. This tendency prompted this study to search for available research documents to examine relevant topics regarding e-government and trust. The method used was a bibliometric analysis by maximising the Vosviewer analysis tool. The data was obtained from the Scopus database. This study reveals the need for further research on the relationship between e-government and trust in Indonesia. These subjects are relatively less explored despite gaining global recognition as vital areas for future research. This unpopularity has contributed to the need for more discussion about the quality of egovernment services regarding the level of trust. Trust is a fundamental aspect of the government system in many countries. The findings of this study encourage a logical consequence to consider factors of trust in implementing e-government in Indonesia in the future. This approach can encourage the government to improve the quality of services and adopt e-government use. Such improvements are expected to bolster trust in the government and sustainably stimulate public interest in its utilisation.